PENERAPAN THINK TALK WRITE UNTUK MENINGKATKAN KEAHLIAN MENULIS BAHASA JERMAN PESERTA DIDIK KELAS X SMAN 1 TAMAN - Nurfadilla, Niken; Pujosusanto, Ari (LATERNE, 2022)
The writing of this article is motivated by the problems of students in classes X Language and X Mathematics and Natural Sciences1, who have difficulty mastering German writing skills. It is known from the results of observations of students’ initial tests in the form of directed essay writing activities on the odd semester "Kennenlernen" theme. Redemittel The formulation of the problem is: is there an increase in the application of think-talk-write to the German writing skills of the tenth graders of SMAN 1 Taman? The purpose of writing this article is to see if there are differences in the learning outcomes of writing skills in German for students of class X semester 1 K.D. 3.1 students of class X between those who apply the learning style and those who do not. The place of research is at SMAN 1 Taman, Sidoarjo. The population in this study were students of class X SMAN 1 Taman, and the samples were class X Language as a control class and class X Mathematics and Natural Sciences1 as an experimental class.The selected article writing method is a true experimental design (pure experiment) in the form of a pretest-posttest control group design. The research data was obtained from the results of the pretest-posttest, which were analyzed by the Mann Whitney test. The results of data acquisition are the posttest average value of the experimental class 89.53 > the control class 88.14 and the Asymp value. Sig. (2-tailed) is 0,001 < 0,05.